Facilitators and barriers to implementation of a pragmatic clinical trial in Aboriginal health services. Issue 1 (6th July 2015) - Liu, Hueming; Laba, Tracey‐Lea; Massi, Luciana; Jan, Stephen; Usherwood, Tim; Patel, Anushka; Hayman, Noel E; Cass, Alan; Eades, Anne‐Marie; Lawrence, Chris; Peiris, David P
Abstract: Objective: To identify facilitators and barriers to clinical trial implementation in Aboriginal health services. Design: Indepth interview study with thematic analysis. Setting: Six Aboriginal community‐controlled health services and one government‐run service involved in the Kanyini Guidelines Adherence with the Polypill (KGAP) study, a pragmatic randomised controlled trial that aimed to improve adherence to indicated drug treatments for people at high risk of cardiovascular disease. Participants: 32 health care providers and 21 Aboriginal and Torres Strait Islander patients. Results: A fundamental enabler was that participants considered the research to be governed and endorsed by the local health service. That the research was perceived to address a health priority for communities was also highly motivating for both providers and patients. Enlisting the support of Aboriginal and Torres Strait Islander staff champions who were visible to the community as the main source of information about the trial was particularly important. The major implementation barrier for staff was balancing their service delivery roles with adherence to often highly demanding trial‐related procedures. This was partially alleviated by the research team's provision of onsite support and attempts to make trial processes more streamlined. Although more intensive support was highly desired, there were usually insufficient resources to provide this. Conclusion: Despite strong community and health service support, major investments in time and resources are needed to ensure successful implementation and minimal disruption to already overstretched, routine services. Trial budgets will necessarily be inflated as a result. Funding agencies need to consider these additional resource demands when supporting trials of a similar nature.